Potensi Pengembangan Budidya Lebah Trigona Sp Di Kecamatan Mowila Kabupaten Konawe Selatan - Muhammad Sofyan Usra; La Ode Arsyad Sani; Achmad Selamet Aku (Fakultas Peternakan Universitas Halu Oleo, 2024)
Trigona sp beekeeping is a business that has been carried out by many people in Mowila District, Konawe Selatan Regency, but not many know about the prospects for developing this business in the future. This study aims to analyze the development potential of Trigona sp honey bees in Mowila District, Konawe Selatan Regency. This research was carried out in July-June 2022 by taking the research location in Mowila District, Southeast Sulawesi Province. The research location was determined purposively (purposive sampling) with the consideration that in a village located in Mowila District, there is a relatively large population developing the Trigona sp beekeeping business. The number of respondents taken in this study was 80 respondents. The analysis used in this research is descriptive analysis using the SWOT analysis technique. The results using the SWOT analysis in this study indicate (1) the S-O strategy (a.) Increasing the relatively good quality of honey in order to increase production and is supported by easy colony maintenance and the availability of plantation crops as a feed source. (b.) Improving infrastructure and supported by local government policies in an effort to promote the processing of Trigona sp. honey bees. (2) W-O strategy (a.) Consumer demand is quite large, extension agents must be more active in conducting training and providing guidance in carrying out Trigona sp honey bee cultivation business puzzles from extension agents. (b.) Forming livestock groups assisted by the active role of extension agents. (3) S-T strategy (a. Supported by easy bee care can increase production so that income can increase.) and (4) W-T strategy (a.) Increase human resource skills so that they can increase the ability of breeders to process Trigona sp. bee cultivation business. (b) Participate in many trainings held by the Animal Husbandry Service or related institutions so that they can overcome the effects of weather and reduce the effect of unstable prices in conducting Trigoan sp. beekeeping.